Christian-Muslim relations: a bibliographical history ; Volume 13: Western Europe (1700-1800) - Thomas, David; Chesworth, John; Bennett, Clinton (History of Christian-Muslim relations, 2019)
Christian-Muslim Relations, a Bibliographical History Volume 13 (CMR 13) covering Western Europe in the period 1700-1800 is a further volume in a general history of relations between the two faiths from the 7th century to the early 20th century. It comprises a series of introductory essays and also the main body of detailed entries which treat all the works, surviving or lost, that have been recorded. These entries provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous leading scholars, CMR 13, along with the other volumes in this series, is intended as a basic tool for research in Christian-Muslim relations. Section editors: Clinton Bennett, Luis F. Bernabé Pons, Jaco Beyers, Emanuele Colombo, Karoline Cook, Lejla Demiri, Martha Frederiks, David D. Grafton, Stanisław Grodź, Alan Guenther, Vincenzo Lavenia, Emma Gaze Loghin, Gordon Nickel, Claire Norton, Radu Păun, Reza Pourjavady, Douglas Pratt, Charles Ramsey, Peter Riddell, Umar Ryad, Mehdi Sajid, Cornelia Soldat, Karel Steenbrink, Ann Thomson, Carsten Walbiner